2018
DOI: 10.1111/jocn.14622
|View full text |Cite
|
Sign up to set email alerts
|

Expert in nursing care but sometimes disrespected—Telenurses’ reflections on their work environment and nursing care

Abstract: If telenurses are to perform good nursing care over the telephone, managers must provide them with resources, for example, support, education and opportunities for recovery during shifts. It seems that the role of the 1177 service has not been properly implemented and accepted within the healthcare system, and politicians need to anchor its mission within the healthcare organisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…Studies about interactional dilemmas are scarce, and knowledge is lacking on what strategies triage nurses apply when they experience absence of congruence. In one Swedish interview study about working environment, it was briefly mentioned that some triage nurses complied to the CDSS because they were afraid of making a wrong assessment (Wahlberg & Bjorkman, ). We also found that management demands were one of the aspects that influenced the choice for the working strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies about interactional dilemmas are scarce, and knowledge is lacking on what strategies triage nurses apply when they experience absence of congruence. In one Swedish interview study about working environment, it was briefly mentioned that some triage nurses complied to the CDSS because they were afraid of making a wrong assessment (Wahlberg & Bjorkman, ). We also found that management demands were one of the aspects that influenced the choice for the working strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In the few studies about interactional workability, which are not specifically about telephone triage nurses, the telemedicine setting both enabled and constrained the nurses' reasoning and decision-making (Barken et al, 2017;Murdoch et al, 2015). When the CDSS does not support the triage view study about working environment, it was briefly mentioned that some triage nurses complied to the CDSS because they were afraid of making a wrong assessment (Wahlberg & Bjorkman, 2018). We also found that management demands were one of the aspects that influenced the choice for the working strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The RNs not only wanted this from GPs, but also asked for support possibilities from colleagues and time for discussions within their own profession. These activities could decrease occupational stress and reduce feelings of loneliness in making telephone assessments [43]. At PHCCs with professional collaboration, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies so far have shown that telenurses experience problems when encountering care-seekers with mental illness problems, as they have nowhere to refer them (cloaked citation during review process). Telenursing is a complex form of nursing care (Snooks et al, 2008, Wahlberg & Bjorkman, 2018 which occurs within a controlled (Röing et al, 2013) and linear structure (Murdoch et al, 2015). The fact that the work procedure of TAN is guided by a CDSS (Ernesäter, Holmström, & Engström 2009) means that the nurses are obligated to reduce the caller's symptoms and problems to something that can be documented within the structure of the CDSS (Murdoch et al, 2015).…”
Section: Rationale and Aimmentioning
confidence: 99%